Business Establishment Opposition to Southern Ireland's Exit from the United Kingdom - Barry, Frank (My University, 2022)
After more than a century of political and economic integration, Southern Ireland exited the United Kingdom in 1922. By identifying the leading business firms of the era and the political and religious allegiances of their owners, this paper explores the perspective of the Southern Irish business establishment on the issues involved. While the mass of the population was Catholic and by 1918 favored secession, the business elite is shown to have been predominantly Protestant and strongly supportive of continued integration. Business elite perceptions of the consequences of exiting the United Kingdom are explored, and post-independence economic and business developments assessed in light of the concerns expressed at the time. The paper also charts the post-independence fate of the leading former unionist firms and the erosion and eventual disappearance of the sectarian divisions then prevalent in Irish business life.
PUBLISHED
Keywords: Nationalism; Economic disintegration; Ireland; Europe 20th; International Development; International Integration; Business history; Development; Globalization; History; Policy